Sarcopenic Obesity: A Growing Public Health Concern – A Literature Review - Anna Maria Jocz; Natalia Katarzyna Wagner-Bieleń; Martyna Zwierzchowska; Agata Antoniak; Anna Centkowska; Joanna Karina Banaśkiewicz; Aleksandra Maria Żyta; Gabriela Helena Dąbrowska; Maria Anna Żmijewska; Jakub Ziółkowski (Quality in Sport, 2025)
Background: Sarcopenic obesity (SO) is a growing clinical and public health concern characterized by the coexistence of excess adiposity and reduced skeletal muscle mass and function. It is increasingly prevalent across various age groups, particularly among individuals with chronic conditions.